PENGARUH TINGKAT MOTIVASI DAN KOMPENSASI TERHADAP KINERJA GURU DI SEKOLAH MENENGAH KEJURUAN LAB BUSINESS SCHOOL KOTA TANGERANG TAHUN PELAJARAN 2018/2019 - Nuraini .; Yusuf Budiana Tanu (Universitas Islam Syekh Yusuf, 2020)
ABSTRACTThis study uses an associative descriptive research method with a quantitative approach with data analysis techniques using multiple regression. The population in this study were the teachers in the Vocational School Business School in Tangerang City and the sample taken by all the teachers in the Vocational School Business School were 47 teachers. Based on the results of research calculations The results of this study indicate in the F test (simultaneous) that the level of motivation and compensation significantly affects teacher performance with a sig value of F 0,000 <0.05 and an F value of 11.221. The results of the t test (partial) showed that the level of motivation significantly affected teacher performance with a sig t value of 0.001 <0.005 and a value of t arithmetic 3652, and compensation significantly affected a teacher's performance with a t value of 0.001 <0.005 and a t value of -3.736. so, it can be concluded that the level of motivation and compensation influences teacher performance both simultaneously and partially. While the determinant coefficient value of the variable obtained R square value of 0.338 shows the contribution of the influence of the independent variable (motivation and compensation) to the dependent (teacher performance) means that motivation and compensation on teacher performance in schools has an effect of 33.8% while the remaining 66.2% is influenced by other variables which did not include within the scope of the study.